2017
DOI: 10.1248/bpb.b17-00226
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the Original Plant Species of Crude Drugs Distributed as Cynanchi Wilfordii Radix and Its Related Crude Drugs in the Korean and Chinese Markets

Abstract: Cynanchi Wilfordii Radix (CWR) is used in Korea as a substitute for Polygoni Multiflori Radix (PMR), which is a crude drug traditionally used in East Asian countries. Recently, the use of Cynanchi Auriculati Radix (CAR) in place of PMR and CWR has emerged a major concern in the Korean market. In Japan, PMR is permitted to be distributed as a pharmaceutical regulated by the Japanese Pharmacopoeia 17th edition (JP17). Although CWR and CAR have not traditionally been used as medicines, CWR was recently introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Although the technological level has dropped, Sheng di huang and Cynanchi wilfordii radix plant increased in the number of patents. The result is consistent with the rapid increase in the demand in the Korean market and the introduction of health foods containing C. wilfordii radix in Japan (Sato-Masumoto et al, 2017). Therefore, it is assumed that the technology level of those medicinal plants will increase in the future since the number of patents associated with those plants were increasing rapidly (WIPS, 2018).…”
Section: Discussionsupporting
confidence: 52%
“…Although the technological level has dropped, Sheng di huang and Cynanchi wilfordii radix plant increased in the number of patents. The result is consistent with the rapid increase in the demand in the Korean market and the introduction of health foods containing C. wilfordii radix in Japan (Sato-Masumoto et al, 2017). Therefore, it is assumed that the technology level of those medicinal plants will increase in the future since the number of patents associated with those plants were increasing rapidly (WIPS, 2018).…”
Section: Discussionsupporting
confidence: 52%
“…CAR resembles CWR closely in appearance as shown in Figure 4 . In this study, CWR and CAR (four and nine samples, respectively) identified using DNA sequences [ 5 ] were used as the test samples ( Table 2 and Figure 4 ). HPLC chromatograms of MeOH extracts (CWR-Ex and CAR-Ex) obtained from these samples are shown in Figure 5 .…”
Section: Resultsmentioning
confidence: 99%
“…CWR and CAR for HPLC and TLC analyses were obtained from the Gyeongdong or Chinese markets and were provided by Japanese crude drug wholesalers. The identities of all the crude drugs were confirmed using DNA sequences [ 5 ]. All other reagents used were of analytical grade.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations